1996
DOI: 10.1074/jbc.271.37.22358
|View full text |Cite
|
Sign up to set email alerts
|

A Capacitative Calcium Current in Cultured Skeletal Muscle Cells Is Mediated by the Calcium-specific Leak Channel and Inhibited by Dihydropyridine Compounds

Abstract: Calcium stores from cultured skeletal muscle cells were depleted using cyclopiazonic acid (CPA), a reversible inhibitor of Ca2+-ATPases at the sarcoplasmic reticulum. Store depletion led to activation of the calcium-specific leak channel, as assayed using single-channel patch clamp analysis and rates of manganese influx and quenching of fura-2 fluorescence. Two novel dihydropyridine compounds inhibited this single-channel leak channel activity, the resting and depletion-induced manganese influx, and refilling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
95
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 73 publications
8
95
1
Order By: Relevance
“…For skeletal muscle cells there had been some controversy. The evidence that skeletal muscle CCE was mediated by a "leak channel" was based on observations of Mn 2ϩ entry, used as a surrogate of Ca 2ϩ (12). However, we observed that Mn 2ϩ entry is not capacitative (14).…”
Section: Complications Of the Existing Cce Models-mentioning
confidence: 66%
See 1 more Smart Citation
“…For skeletal muscle cells there had been some controversy. The evidence that skeletal muscle CCE was mediated by a "leak channel" was based on observations of Mn 2ϩ entry, used as a surrogate of Ca 2ϩ (12). However, we observed that Mn 2ϩ entry is not capacitative (14).…”
Section: Complications Of the Existing Cce Models-mentioning
confidence: 66%
“…We had previously shown that CCE occurs in L6 skeletal muscle cells (11), and others demonstrated subsequently that CCE occurs in skeletal muscle (12,13). In our prior studies of L6 cells, we determined Ca 2ϩ in both cytosol and ER using fluorescent dyes, finding that Ca 2ϩ enters the ER even in the presence of thapsigargin (14).…”
mentioning
confidence: 92%
“…Other myotube studies have established a link between mitochondrial depolarization and reduced SOCE (Vandebrouck et al 2006) or sarcolemmal TRPC1 channels anchored to the dystrophin-associated glycoprotein complex via α1-syntrophin with compromised SOCE in dystrophic myotubes where this molecular lattice would be disrupted (Vandebrouck et al 2007). Another early study found a store-dependent capacitive Ca 2+ current in cultured myotubes that was mediated by Ca 2+ -specific leak channels and, interestingly, inhibited by dihydropyridines (Hopf et al 1996).…”
Section: Store-operated Ca 2+ Entry (Soce) In Skeletal Musclementioning
confidence: 99%
“…Another concern in most electrophysiological cellattached patch clamp studies connecting SOCE to plasma membrane Ca 2+ influx is the use of >100 mM Ca 2+ concentrations in the pipettes that vastly increase driving force both in myotubes (Hopf et al 1996) and adult fibers. In this regard, Allard et al (2006) challenged the physiological role of store-operated membrane conductance in adult skeletal muscle by showing no increase in whole cell conductance or single channel activity in single fibers severely depleted by prolonged depolarizing pulses under voltage-clamp conditions, either in the presence or in the absence of CPA or in the presence of 25 mM caffeine (Allard et al 2006).…”
Section: Store-operated Ca 2+ Entry (Soce) In Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation